The Influence of Service Innovation and Service Quality on Customer Satisfaction Users of Mobile Banking Livin' by Mandiri - Marsya, Amanda; Hambalah, Febrina (UMSurabaya Publishing, 2024)
This research was conducted with the aim of determining the influence and analyzing service innovation and service quality on customer satisfaction among Livin' by Mandiri mobile banking users. Using a quantitative approach with a survey method using SPSS version 27 tools. Primary data is used as a data source in form of a questionnaire from respondent responses with sampling using purposive sampling using the Slovin formula, then a sample of 99 respondents was obtained. The result show that simultaneously service innovation and service quality have a positive and significant effect on customer satisfaction for Livin' by Mandiri. It is hoped PT Bank Mandiri will always develop service innovation and service quality that is easier, faster, more accurate and comfortable by following technological developments so that it has an impact on increasing customer satisfaction.